Новый подвид ящурки глазчатой — Eremias multiocellata bannikowi ssp. n. (Reptilia, Sauna) из Тувы и Северо-Западной Монголии - Щербак, H.H. (Вестник зоологии, 1973)
Study of samplings from populations of the species areal for E. multiocellata shows, that some of them may be united into subspecies (except for nominal one): E. m. kozlowi, E. m. yarkandensis and E. m. bannikowi ssp. n. The table for determination of the E. multiocellata subspecies and a description of the new subspecies are presented.